Evaluation of facilities management sustainable parameters for improving operational efficiency. Issue 5 (4th May 2021) - Islam, Rashidul; Nazifa, Tasnia Hassan; Mohamed, Sarajul Fikri
Abstract: Sustainability is becoming an integral part of the life-cycle development of built facilities and is emphasized during the design phase and post-occupancy phase. This article, therefore, investigates the facilities management (FM) sustainable parameters impact on cost performance of building projects. The sustainable parameters were identified through a systematic review of literature and these were separated into four categories: people, process, economy and social. This study was followed by a questionnaire survey and 31 respondents graded them in a 5-point Likert scale during the online survey. The mean and relative significance index of the sustainable parameters were determined, followed by rank analysis. The research findings show that cost-effectiveness, value of asset, environmental, practiced culture and design adaptability are widely accepted as sustainable parameters in FM practice. The study findings also show that maintainability was rated as very significant in design process for reducing long-term cost. The relationships between sustainable parameters and consideration in building design were identified using correlation tests. Finally, this research concludes that the integration of sustainable parameters and maintainability consideration into the design phase are capable to reduce 15–20% maintenance costs in building projects. This study provides an insight into the most significant design consideration and sustainable parameters for achieving operational efficiency.